2018
DOI: 10.1055/s-0038-1669929
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Medial Tibial Slope on Anterior Tibial Translation and Short-Term ACL Reconstruction Outcome

Abstract: Background  Increased tibial slope has been shown to be associated with higher anterior cruciate ligament (ACL) reconstruction failure rate. Little is known about the correlation of tibial slope and anterior tibial translation in ACL deficient and reconstructed knees as well as the correlation of tibial slope and ACL reconstruction outcome. Purpose/Hypothesis  The purpose of this study was to investigate the correlation of tibial slope with anterior tibial translation and ACL reconstruction outcome. It is hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…When there is a loss of feedforward muscular activation control, for instance at foot positions that occur in a very short time span, an ACL (re)injury may occur in patients with a large PTPA because forces are not carried by the muscular components. This is in line with previous studies that showed that the PTPA correlates with an increased ATTp in ACL injured, ACL reconstructed and cadaveric knees [ 5 , 13 , 28 ]. We did find a significant CCA correlation between the LPTPA and muscle activation, which suggests that patients indeed amend their muscle activation to the anatomy of their knee, especially by reducing their medial hamstring activity when the LPTPA is larger.…”
Section: Discussionsupporting
confidence: 93%
“…When there is a loss of feedforward muscular activation control, for instance at foot positions that occur in a very short time span, an ACL (re)injury may occur in patients with a large PTPA because forces are not carried by the muscular components. This is in line with previous studies that showed that the PTPA correlates with an increased ATTp in ACL injured, ACL reconstructed and cadaveric knees [ 5 , 13 , 28 ]. We did find a significant CCA correlation between the LPTPA and muscle activation, which suggests that patients indeed amend their muscle activation to the anatomy of their knee, especially by reducing their medial hamstring activity when the LPTPA is larger.…”
Section: Discussionsupporting
confidence: 93%
“…21,24 Furthermore, the relationship between PTS and graft tear (as opposed to primary ACL injury) has been examined in fewer studies, with varying results. 4,15,17,21 Even fewer studies have examined the relationship between PTS and graft tear in the setting of revision ACL reconstruction. 12…”
Section: Discussionmentioning
confidence: 99%
“…14,21 Yet others have found significance for either the medial tibial slope alone or both the medial and the lateral tibial slopes being higher in patients with ACL injury. 3,7,12,15,17,22,26 Furthermore, the relationship between the PTS and graft or contralateral ACL injury in patients undergoing reconstruction specifically with patellar tendon autograft (PTG) has not been extensively reported.…”
mentioning
confidence: 99%
“…Interestingly, further work has demonstrated that an increase in posterior slope is associated with greater anterior tibial translation in ACL-deficient knees. 8,41 These studies highlight the complex interplay between various bony and soft tissue structures within the knee and the influence that they have in determining knee kinematics and restraint to deformity.…”
Section: Discussionmentioning
confidence: 99%